x2 + 8x = -15
x2 + 8x + 15 = 0 since 15 = 5 x 3 and 5 + 3 = 8, then
(x + 5)(x + 3) = 0
x + 5 = 0 or x + 3 = 0
x = -5 or x = -3
x2 + 8x + 15 = (x + 3) (x + 5).
(x-3)(x-5) = 0
8x+39 = 2x-15 6x = -54 x = -9
2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14
8x plus 4y equals 5 is 8x + 4y = 5.
x2 + 8x + 15 = (x + 3)(x + 5)
x2 + 8x + 15 = (x + 3) (x + 5).
(x-3)(x-5) = 0
3 is a factor and dividing by 3 gives x + 15 = 8x
x2-8x+15 = (x-3)(x-5)
8x = 2x + 15 6x = 15 x = 15/6 = 2.5
X = 1
8x+39 = 2x-15 6x = -54 x = -9
Y-8x plus 9y equals 10y-8x.
2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14
8x plus 4y equals 5 is 8x + 4y = 5.
the empty set.